PERANCANGAN DAN PENERAPAN LEAN MAINTENANCE MANAGEMENT DI PT. HAPETE SURABAYA - Stevan Wijaya; Dina Natalia Prayogo; Mochammad Arbi Hadiyat (Perpustakaan Universitas Surabaya, 2018)
PT. Hapete is a company engaged in manufacturing yarn and rope. PT. Hapete has three production divisions, namely Doubling, Twisting and Winding. Winding division been the focus of research because it has the largest engine damage frequency in the company. The purpose of this study is to determine the optimal maintenance schedule that takes into age of the components and cost as well as designing lean maintenance systems to minimize waste and improve the efficiency of maintenance activities. The result of the calculation of maintenance value stream map (MVSM) shows the range of maintenance efficiency before and after repairs are respectively 19-35% and 27-42% with an average increase of 7.89%. Increased maintenance efficiency is affected by the implementation of 5S in the workshop and spare parts warehouse. Conditions workshop and warehouse tidy with clear instructions make it easy for workers looking for a tool or component is needed, thus shortening the delay that occurs during engine repairs done. For the calculation of overall equipment effectiveness (OEE) shows the average value of OEE before and after repairs are respectively 77.78% and 84.74% with an average increase of 6.96%. Increasing the value of OEE is affected by the implementation of new work instructions and standards by operators and mechanics, autonomous maintenance by operators, as well as the training undertaken to improve the ability of the operator to operate the machine. Such repair can improve the performance of workers and machines that have an impact on increasing the effectiveness.